Individualized Patient-Progress Systems: Why We Need to Move Towards a Personalized Evaluation of Psychological Treatments - Sales, Célia M. D. (2014)
Patient-focused psychotherapy research refers to the monitoring, prediction, and evaluation of patient progress in therapy. This is traditionally based on repeated standardized measurement and followed by the provision of nomothetic feedback to both therapists and patients based on those measures. Patient progress throughout therapy can also use idiographic assessments, which involve using personalized instruments to elicit information that is truly specific to each patient. This article introduces the concept of individualized progress research, which combines nomothetic and idiographic measures, and presents the individualized patient-progress system (IPPS; Sales et al., 2011, 2011a, 2011b), a hybrid patient-progress system. There are benefits to using a hybrid approach: Nomothetic instruments compare clients whereas idiographic assessments provide a better understanding of each clinical case. Preliminary feedback of therapists piloting the IPPS suggests that this system is helpful to clinical tasks such as monitoring individual-family-group psychotherapy change, assisting clinicians in addressing patients' realistic needs, and stimulating patients' self-reflection about therapy.